Current status of simulation-based training tools in general surgery: A systematic review. (January 2022) - Shah, Salonee; Aydin, Abdullatif; Fisher, Rebecca; Ahmed, Kamran; Froghi, Saied; Dasgupta, Prokar
Abstract: Background: The use of simulation-based training tools within surgery is rapidly increasing and has demonstrated promising alternative training modalities allowing for surgical skill enhancement despite workplace pressures. Whilst many simulators have been investigated for their validity, this has not been demonstrated across all domains. This review aims to identify the status of simulation-based training tools in general surgery in the current literature, assess their validity and determine their effectiveness. Methods: OVID Medline and Embase databases were searched for English language articles describing the validation of a simulator for general surgery-specific procedures between 2000 and 2020. Studies were reviewed according to Messick's validity framework and rated in each domain. A modified version of translational outcomes described by McGaghie et al. were used to determine the level of effectiveness (LoE) of each simulator. Results: A total of 9653 articles were screened and 97 articles were identified to determine the LoE of the simulators. The highest rating for each validity domain was achieved by 30 models/training courses for content validity, 48 for response processes, 5 for internal structure, 40 for relations to other variables and 10 for consequences. Two simulators gained LoE >2 showing skill transfer downstream of the simulator. Conclusion: The varying ratings across each validity domain for the simulators show that evidence of complete validity is poor. Only 2 simulators were awarded LoE >2, indicating further research is needed in order to substantiate the use of simulation in improving patient outcomes. Highlights: Use of simulation-based training tools in general surgery is rapidly increasing. This review aims to identify the current status of simulation-based training tools. Validity and effectiveness have been determined for training in general surgery. Ratings across each simulator domain show evidence of complete validity is poor. Further research is needed to substantiate simulator use to improve outcomes.